Multimodal Adapter Evolution: Honey Badger Algorithm for Scientific Foundation Model Fine-Tuning - Takaaki Fujita1; Bilal A. Khan2 (Metaheuristic Algorithms with Applications, 2026)
This paper introduces MAE-HBA, a novel metaheuristic optimization algorithm designed to address Riemannian manifold-constrained optimization. The proposed approach leverages Honey Badger Algorithm + adapter evolution to achieve robust and efficient performance across diverse problem instances. Unlike existing methods that rely on fixed search operators and static parameter configurations, MAE-HBA incorporates adaptive mechanisms that dynamically adjust the search strategy based on real-time landscape analysis. We provide a rigorous theoretical framework establishing convergence guarantees under mild assumptions, along with a detailed complexity analysis demonstrating the algorithm's computational efficiency. The experimental evaluation employs adversarial perturbation of problem landscape; adversary optimizes worst-case disruption, featuring game-theoretic adversarial robustness. Statistical significance is assessed using Bayesian factor + Wilcoxon signed-rank, with effect size reporting to quantify practical significance. Results demonstrate that MAE-HBA achieves statistically significant improvements over nine state-of-the-art baselines, with an average performance gain of 22.5% and large effect sizes (Cohen's d > 0.8). Ablation studies confirm the contribution of each algorithmic component, and sensitivity analysis identifies the most influential parameters. The framework is validated on real-world problem instances, demonstrating practical applicability and robustness under varying conditions.